Collaborative modelling to support forest management: qualitative systems analysis at Lumut Mountain, Indonesia - Purnomo, H.; Yasmi, Yurdi; Prabhu, Ravi; Hakim, S.; Jafar, A.; Suprihatin (2003)
Complex ecological and social processes in tropical forests imply that observations on any single element of the system do not provide an adequate basis for sound forest management. A collaborative modelling process engaging all relevant stakeholders led to a shared understanding of how to manage forests around Lumut Mountain, Pasir distrcit, East Kalimantan, Indonesia. The model was developed by identifying forest management objectives, building a conceptual model using a causal loop diagram, and defining performance indicators. The model was then used to explore future scnarios to improve the well-being of local stakeholders while maintaining forest quality. Finally, roles needed to implement the chosen scenarios were defined and assigned to individual participants. This qualitative modelling process was found to be an effective way to assist the development of a collborative action plan.